The effect of radiation dose rate on radiosensitization potential of PEG-coated bismuth oxide nanoparticles: A nanoscopic biodosimetry by DNA plasmid - Farshad Seyednejad; Elham Mansouri; Asghar Mesbahi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2025)
Background. Nanoparticle-based radiation therapy using metal nanoparticles is an adjuvant therapy that makes tumor cells more sensitive to radiation. In this study, we have used plasmid to study the effect of radiation dose rate on the amount of radiation sensitization of bismuth oxide nanoparticles. Methods. In this study, bismuth oxide nanoparticles coated with polyethylene glycol were used as megavoltage radiation sensitizers. In this research, we used DNA plasmid PCEP4-102 as a nanoscopic dosimetry probe to measure the radiation sensitization effect of metal nanoparticles in radiation therapy. Plasmid samples with and without coated nanoparticles were irradiated with 6 megavolt X-rays at dose rates of 50 MU/min and 833 MU/min. Results. The dose enhancement factor for plasmid samples containing Bi2O3 nanoparticles irradiated with 6 megavolt X-rays was 1.33 ± 0.1. Increasing the dose rate from 50 MU/min to 833 MU/min did not cause any obvious change in the amount of plasmid damage in the plasmid samples without nanoparticles. Considering the plasmid samples containing metal nanoparticles, the values of the dose enhancement factor for the samples exposed to 6MV X-ray irradiation at a dose rate of 833 MU/min were significantly increased compared to the samples irradiated with 6 MV X-rays at a dose rate of 50 MU/min. Conclusion. This study confirms the efficiency of bismuth oxide nanoparticles in increasing the effectiveness of radiation therapy. In the presence of nanoparticles, increasing the dose rate can cause more damage to the plasmid by chemical and physicochemical enhancement in radiation therapy by megavolt photons. Practical Implications. The results of this study confirm the radiosensitization potential of metallic nanoparticles and show that increasing the dose rate leads to an increase in the damaging effect of nanoparticle-aided radiation therapy.